Measuring resilience properties of household livelihoods and food security outcomes in the risky environments of Ethiopia - Tesfahun A. KASIE; Enyew A. TSEGAYE; Antonio GRANDÍO-BOTELLA; Isabel GIMÉNEZ-GARCÍA (Revista Iberoamericana de Estudios de Desarrollo)
The purpose of this case study, conducted in Amhara region of Ethiopia, is to contribute to efforts to measuring and assessing resilience properties of household livelihoods constructed in the risky environments. It provides new insights for assessing livelihood vulnerability and designing resilience building programs in areas of protracted food crisis. Based on resilience theory as applied to social-ecological systems with an application of Modern Portfolio Theory, we adapted and measure the four properties of resilience to livelihood systems and tested the expected relationships between system properties as predicted by resilience theory. Household livelihood systems exhibited the expected pattern of increasing connectivity with increasing wealth (food income). Similarly, household resilience to food insecurity improves with increasing diversity of livelihood options and diversity declines with increasing connectivity of the system. This study demonstrates the use of a set of metrics for assessing resilience properties of household livelihoods based on key driving factors.